Treatment-resistant schizophrenia : the relationship between clozapine plasma concentration and clinical outcome - I. Kammoun; R. Jouini; A. Aissa; R. Boukhchina; Y. Zgueb; E. Khelifa; U. Ouali; R. Jomli; F. Nacef; Z. El Hechmi (European Psychiatry, 2022)
Introduction Clozapine is highly effective in patients with treatment-resistant schizophrenia but, to ensure optimal clinical response it is important to optimize its use and this depends on adequate pharmacological monitoring.